PENGARUH DIKLAT,KOMUNIKASI DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI SATRIYA COTTAGES KUTA - I Made Hedy Wartana (Institut Pariwisata dan Bisnis Internasional, 2012)
One of many important factors that has a role in the activities of an institution is human resources. The results of analysis in this study shows that education and training, communication and leadership has positive as well as partial and simultaneous significant impact on employee productivity Satriya Cottages in Kuta. This can be seen in the results of multiple linear regression equations were obtained: Y = 5.221 + 0.297 X1 + 0.288 X2 + 0.266 X3, t count of 3.938; 2.863 and 2.102> t Table at 1.6741, the value of p1 = 0.000, p2 = value value of 0.006 and p3 = 0.040 <0.05, F count of 82.029> F table at 3.1716 and sig.F of 0.000 <0.05. Diklat most dominant influence on employee productivity Satriya Cottages in Kuta.